Innovations in on-demand audio education: Beyond trending. (7th April 2020) - Ratliff, Jeffrey; Crowell, Jason; Clardy, Stacey L.; Burns, Ted
Abstract : The evolution of broadcast audio has been rapidly changing over the past 10–15 years with the advent of podcasts in the early 2000s. As with other media, podcast audio has been adapted for use within medical and specifically neurology education in the form of the Neurology Podcast since 2007. As podcasts were an initial step in the field of on-demand media, further technological evolution has resulted in increasing customization of a listener's audio experience. We believe a historical inflection point has been reached with the increasingly mainstream adoption of virtual assistant technology which allows for consumption of brief on-demand self-curated audio productions. As editors of the Neurology Podcast, we have introduced a new audio product to this technological landscape, the Neurology Minute. In doing so, we hope that curated on-demand educational audio will become a part of the daily routine of many practicing neurologists as we move into this new technological age.